Euglossa natesi n. sp., a new species of orchid bee from the Chocó region of Colombia and Ecuador (Hymenoptera: Apidae) - Parra-H, Alejandro; Ospina-Torres, Rodulfo; Ramírez, Santia (Zootaxa, 2006)
A new species of orchid bee in the genus Euglossa is here described. Euglossa natesi n. sp. ParraH, Ospina-Torres & Ramírez has been collected from the Pacific Andean foothills of Colombia and Ecuador. Euglossa natesi n. sp. has no obvious close relatives, and while most morphological characters suggest that it belongs to the subgenus Glossura, a few characters indicate that it belongs to the subgenus Glossurella.